Microbiological tests of fresh bull semen collected at breeding establishment - M. A. Sushkova; I. Ya. Stroganova; S. А. Schislenko (Ветеринария сегодня)
Bacterial and fungal contamination of the semen collected in production environment largely depends on the sanitary conditions of its collection as well as on the bacteria carrier state in breeding bulls. Since antimicrobials contained in the diluent used during semen product cryopreservation do not allow an objective assessment of semen contamination, a microbiological testing of fresh undiluted bull semen was carried out at the AO «Krasnoyarskagroplem» breeding establishment to identify the contamination source. The isolated opportunistic microorganism cultures were tested for their susceptibility to antibiotics for the purpose of effective treatment of bacteria carriers. The experiment was performed at the Department for Epizootiology, Microbiology, Parasitology and Veterinary and Sanitary Expertise of the Institute of Applied Biotechnology and Veterinary Medicine of the FSBEI HE «Krasnoyarsk State Agrarian University» and at the Veterinary Laboratory of the AO «Krasnoyarskagroplem» in 2017 and 2018. Semen was collected in accordance with GOST 32222-2013 and tested for veterinary and sanitary parameters according to GOST 32198-2013. Isolated microorganism cultures were tested for their susceptibility to antibiotics with disc-diffusion method according to the Methodical Guidelines 4.2.1890-04 «Testing of microorganisms for their susceptibility to antimicrobials» using discs containing eight antimicrobials. Analysis of microbiological test results showed that semen was rejected for sanitary reasons at the breeding establishment due to isolation of the following opportunistic microorganisms: Pseudomonas aeruginosa (6.4% samples) and Proteus vulgaris (8.5% sample) in 2017 and Pseudomonas aeruginosa (2.4% samples) in 2018. Other test parameters (total microbial count, coliform count) were within admissible limits. № anaerobes and pathogenic fungi were detected. Four Pseudomonas aeruginosa isolates and three Proteus vulgaris isolates recovered during the test have demonstrated susceptibility to ciprofloxacin that can be used for etiotropic treatment of bulls identified as bacteria carriers.